2008
DOI: 10.1111/j.1747-0765.2008.00289.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 18S rDNA primers for estimating fungal diversity in agricultural soils using polymerase chain reaction-denaturing gradient gel electrophoresis

Abstract: Direct DNA extraction followed by 18S rDNA polymerase chain reaction-denaturing gradient gel electrophoresis (PCR-DGGE) is widely used for the analysis of fungal diversity in agricultural soil ecosystems. Various PCR primer sets have been used for fungi, but few reports have compared the properties of the primers. We investigated the properties of four widely used primer sets for fungal 18S rDNA DGGE: (1) NS1/GCFung, (2) FF390/FR1(N)-GC, (3) NS1/FR1(N)-GC (for single PCR) and (4) NS1/EF3 for the first PCR and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(49 citation statements)
references
References 25 publications
1
48
0
Order By: Relevance
“…The 18S rRNA genes were PCR amplified using the NS1 and EF3 primers (Hoshino & Morimoto 2008). The PCR programme was conducted with an initial denaturation at 94°C for 120 s, followed by 25 cycles of 15 s denaturation at 94°C, annealing for 30 s at 47°C and an extension at 72°C for 120 s followed by a final extension of 8 min.…”
Section: S3: Dna Extraction and Pcr/dgge Analysismentioning
confidence: 99%
“…The 18S rRNA genes were PCR amplified using the NS1 and EF3 primers (Hoshino & Morimoto 2008). The PCR programme was conducted with an initial denaturation at 94°C for 120 s, followed by 25 cycles of 15 s denaturation at 94°C, annealing for 30 s at 47°C and an extension at 72°C for 120 s followed by a final extension of 8 min.…”
Section: S3: Dna Extraction and Pcr/dgge Analysismentioning
confidence: 99%
“…These results suggested that a smaller number of PCR cycles worked better. When using primer sets FF390/FR1(N)-GC and NS1/FR1(N)-GC; however, high PCR cycle numbers are needed to obtain enough product, because the efficacy of the amplification is low (Hoshino & Matsumoto, 2008). Reducing chimera formation is required to provide a more accurate estimation of community diversity.…”
Section: Pcr Amplification and Chimera Formationmentioning
confidence: 99%
“…On the other hands, NS1/GCFung and FF390/FR1-GC produced separate and single bands. We evaluated primer sets for fungal 18S rDNA DGGE using agricultural soils in terms of the following features: detection and reproducibility of DGGE banding profiles, obtained diversity indices, and ability to discriminate fungal communities by DGGE (Hoshino & Matsumoto, 2008). Four primer sets, i.e., for single PCR, NS1/GCFung, FF390/FR1(N)-GC, and NS1/FR1(N)-GC; and for nested PCR, NS1/EF3 for the first PCR and NS1/FR1(N)-GC for the second PCR, were compared using six soil samples from upland (F1, F2, F3 and F4) and paddy fields (P1 and P2) in Japan (Fig.…”
Section: Applicability For Dggementioning
confidence: 99%
“…Due to variations in the rates at which DNA molecules with different sequences denature, molecules of similar size but with variations in sequence can be separated by electrophoresis in a gel containing a denaturing agent in a concentration gradient. This technique is useful for analyzing populations of rRNA genes in soil samples (Hoshino and Morimoto 2008;. Bacterial 16S rRNA genes in the extracted DNA were amplified using the primers 968f-GC (5 0 -CGC CCG GGG CGC GCC CCG GGC GGG GCG GGG GCA CGG GGG GAA CGC GAA GAA CCT TAC-3 0 ) and 1378r (5 0 -CGG TGT GTA CAA GGC CCG GGA ACG -3 0 ) (Heuer et al 1999).…”
Section: Dna Extraction and Dgge Analysismentioning
confidence: 99%
“…Bacterial 16S rRNA genes in the extracted DNA were amplified using the primers 968f-GC (5 0 -CGC CCG GGG CGC GCC CCG GGC GGG GCG GGG GCA CGG GGG GAA CGC GAA GAA CCT TAC-3 0 ) and 1378r (5 0 -CGG TGT GTA CAA GGC CCG GGA ACG -3 0 ) (Heuer et al 1999). Fungal 18S rRNA genes were amplified using the primers NS1 (5 0 -GTA GTC ATA TGC TTG TCT C -3 0 ) and GCFung (5 0 -CGC CCG CCG CGC CCC GCG CCC GGC CCG CCG CCC CCG CCC CAT TCC CCG TTA CCC GTT G -3 0 ) (Hoshino and Morimoto 2008). The DGGE marker III (Nippongene, Toyama, Japan) was used for the bacterial DGGE analysis, and DGGE marker IV (Nippongene) was used for the fungal DGGE analysis.…”
Section: Dna Extraction and Dgge Analysismentioning
confidence: 99%